Identification of beauty and charm quark jets at LHCb - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of Instrumentation, 2015)
Identification of jets originating from beauty and charm quarks is important for measuring Standard Model processes and for searching for new physics. The performance of algorithms developed to select b- and c-quark jets is measured using data recorded by LHCb from proton-proton collisions at √s = 7 TeV in 2011 and at √s = 8 TeV in 2012. The efficiency for identifying a b(c) jet is about 65%(25%) with a probability for misidentifying a light-parton jet of 0.3% for jets with transverse momentum pT > 20GeV and pseudorapidity 2.2 < η < 4.2. The dependence of the performance on the pT and η of the jet is also measured.
LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, P. d'Argent, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, K. Matthieu, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, C. Voß, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 675 weitere]
Gesehen am 11.05.2021